Peran Regulasi Komunikasi dalam Mengatasi Pencurian Data Nasional pada 2024 - Tanjung, Muhammad Farrel; Febrianisa, Fadilla (Jurnal Mahasiswa Komunikasi Cantrik, 2024)
This study examines the impact of national data theft by hackers in 2024 by identifying weak communication regulations. The study was conducted using a qualitative approach with a case strategy. The study results found the need for strict regulations to protect sensitive data by emphasizing that clear and consistently implemented policies can reduce the risk of data theft. The case studies analyzed showed that weak passwords significantly increased vulnerability to attacks, illustrating the need for better education and implementation of stronger security practices. In conclusion, this study underscores the importance of effective regulations in addressing cyber threats and improving the protection of personal information in today's digital era.